A Survey on Digital Rights Management in Distance Education - Singh, Ajit Kumar; Karforma, Sunil; Mukhopadhyay, Sripati (International Journal of Computer Sciences and Engineering, 2025)
The basic purpose of Distance Education (DE) is to provide quality education regardless of time and space for those who do not continue his/her education in traditional mode due to several reasons. In the digital era, DE uses Digital Rights Management (DRM) to promote quality teaching for all. DRM manages and protects any digital creation, in the education domain, it is used to protect and manage Intellectual Property Rights (IPR). There are many distance education system running around the globe and spreading the essence of quality teaching. In our survey we try to focus on DE, DRM, needs of DRM in DE and discuss some pioneer DE systems that use DRM worldwide and also propose a model DRMSDE for Distance Education system using DRM.